Understanding Values Work Institutional Perspectives in Organizations and Leadership - Askeland, Harald; Espedal, Gry; Jelstad Løvaas, Beate; Sirris, Stephen (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
At the core of institutional theories, 'values' is a central term and figures in most definitions; however it remains understudied and under-explored. The editors of this open access book identify a resurgence of interest in the values-construct which underpins discussions of identity, 'ethos' and the purpose/nature of public and civic welfare provision. Considering the importance of values and values work to social, material and symbolic work in organizations, individual chapters explore values work as performed in organizations and by leaders. Focusing on practices of values work, the book applies and combines different theoretical lenses exemplified by the integration of institutional perspectives with micro-level perspectives and approaches. Harald Askeland is Professor of Organization and Management at VID Specialized University, Norway. His research interests span issues such as reform implementation, change management, leadership roles, and managerial work. He has edited books on leadership and values-based leadership and published articles in both national and international journals. Gry Espedal is Associate Professor at VID Specialized University, and holds a Master of Management. She researches values work in institutions and processes of institutionalization in organizations pressured by changing macro-contexts. She has published articles and books within values-based leadership, authentic leadership, values work, coaching and solution-focused approach. Beate Jelstad Løvaas is Associate Professor at VID Specialized University. She has published in national and international journals. Her current research interests include relational leadership, meaningful work and motivation, and the role of values in nonprofit organizations, and in the public and private sector. Stephen Sirris is Associate Professor and Head of the Master's programme in Values-based leadership and Centre of Values-based Leadership and innovation at VID Specialized University, Oslo. He has published on leadership and organization in the third sector with an emphasis on religious organizations, volunteers, professionals and the role of values.